Intervention for Prevention of Exacerbation on Chronic Obstructive Pulmonary Disease (COPD) Patients - Iwan Shalahuddin; Sandra Pebrianti; Theresia Eriyani (Universitas Aisyah Pringsewu, 2021)
COPD is the leading cause of morbidity and mortality worldwide Worsening symptoms of COPD or what is called acute exacerbations are common occurrences that often lead to hospitalization, and the frequency gets worse as the disease progresses. Often associated with a deteriorating quality of life, increased health care costs, and increased mortality. The purpose of searching for articles is to obtain articles from Indonesia or abroad that discuss effective methods in relieving exacerbation symptoms of chronic obstructive pulmonary disease. This study uses a literature review method approach that is suitable for use in this literature study is a scoping review because the purpose of this literature study is to determine an effective method in relieving exacerbation symptoms of the chronic obstructive pulmonary disease so that it can be used as an alternative method of handling exacerbation symptoms in patients with disease chronic obstructive pulmonary. A literature search using several sources, namely Ebscoshot, Google Scholar and Pubmed. Literature search results. The most nutritional deficiencies in COPD patients are vitamin B12 and vitamin D deficiency. Based on 10 journals on interventions in patients with COPD, vitamin D intake is a more effective intervention than other interventions. The number of COPD exacerbations in the intervention group with vitamin D intake decreased significantly compared to the control group (P-value less than 0.001). In addition, FEV1 in the intervention group increased compared to the control group that experienced a decrease (P-value less than 0.001). Recommendations for nurses play an important role in administering medication, including the provision of vitamin D interventions as a result of collaboration with doctors to patients. The nurse should know all the components of the drug order and question the order if it is incomplete or unclear or the dose is outside the recommended limit. Abstrak: PPOK adalah penyebab utama morbiditas dan mortalitas di seluruh dunia. Gejala PPOK yang memburuk atau biasa disebut Eksaserbasi akut adalah kejadian umum yang sering menyebabkan rawat inap, dan frekuensinya memburuk seiring dengan perkembangan penyakit. Sering dikaitkan dengan kualitas hidup yang memburuk, peningkatan biaya perawatan kesehatan, dan peningkatan kematian. Tujuan dari pencarian artikel yaitu untuk mendapatkan artikel dari Indonesia ataupun luar negeri yang membahas mengenai metode efektif dalam meringankan gejala eksaserbasi penyakit paru obstruktif kronis. Penelitian ini menggunakan pendekatan metode literatur review yang sesuai untuk digunakan dalam studi literatur ini adalah scoping review dikarenakan tujuan dari studi literatur ini adalah untuk mengetahui metode efektif dalam meringankan gejala eksaserbasi penyakit paru obstruktif kronis, sehingga dapat digunakan sebagai metode alternatif penanganan gejala eksaserbasi pada pasien penyakit paru obstruktif kronis. Pencerian literatur dengan menggunakan beberapa sumber yaitu Ebscoshot, Google Scholar dan Pubmed.. Hasil penelusuran literatur. Kekurangan nutrisi paling banyak oleh pasien PPOK adalah defisiensi vitamin B12 dan vitamin D. Berdasarkan 10 jurnal mengenai intervensi pada pasien dengan PPOK, pemberian asupan Vitamin D menjadi intervensi yang lebih efektif dibandingkan intervensi lainnya. Jumlah eksaserbasi PPOK pada kelompok intervensi pemberian asupan vit D menurun secara signifikan dibandingkan dengan kelompok kontrol (P value kurang dari 0,001). Selain itu FEV1 pada kelompok intervensi mengalami peningkatan dibandingkan dengan kelompok kontol yang mengalami penurunan (P value kurang dari 0.,001). Rekomendaasi untuk perawat berperan penting dalam memberikan obat-obatan termasuk dalam pemberian intervensi vitamin D sebagai hasil kolaborasi dengan dokter kepada pasien. Perawat harus mengetahui semua komponen dari perintah pemberian obat dan mempertanyakan perintah tersebut jika tidak lengkap atau tidak jelas atau dosis yang diberikan di luar batas yang direkomendasikan